First off‐time treatment prostate‐specific antigen kinetics predicts survival in intermittent androgen deprivation for prostate cancer. Issue 1 (26th October 2015) - Sanchez‐Salas, Rafael; Olivier, Fabien; Prapotnich, Dominique; Dancausa, José; Fhima, Mehdi; David, Stéphane; Secin, Fernando P.; Ingels, Alexandre; Barret, Eric; Galiano, Marc; Rozet, François; Cathelineau, Xavier
Abstract : BACKGROUND: Prostate‐specific antigen (PSA) doubling time is relying on an exponential kinetic pattern. This pattern has never been validated in the setting of intermittent androgen deprivation (IAD). Objective is to analyze the prognostic significance for PCa of recurrent patterns in PSA kinetics in patients undergoing IAD. METHODS: A retrospective study was conducted on 377 patients treated with IAD. On‐treatment period (ONTP) consisted of gonadotropin‐releasing hormone agonist injections combined with oral androgen receptor antagonist. Off‐treatment period (OFTP) began when PSA was lower than 4 ng/ml. ONTP resumed when PSA was higher than 20 ng/ml. PSA values of each OFTP were fitted with three basic patterns: exponential (PSA(t) = λ.e αt ), linear (PSA(t) = a.t), and power law (PSA(t) = a.t c ). Univariate and multivariate Cox regression model analyzed predictive factors for oncologic outcomes. RESULTS: Only 45% of the analyzed OFTPs were exponential. Linear and power law PSA kinetics represented 7.5% and 7.7%, respectively. Remaining fraction of analyzed OFTPs (40%) exhibited complex kinetics. Exponential PSA kinetics during the first OFTP was significantly associated with worse oncologic outcome. The estimated 10‐year cancer‐specific survival (CSS) was 46% for exponential versus 80% for nonexponential PSA kinetics patterns. The corresponding 10‐year probability of castration‐resistant prostate cancer (CRPC) was 69% and 31% for the two patterns, respectively. Limitations include retrospective design and mixed indications for IAD. CONCLUSION: PSA kinetic fitted with exponential pattern in approximately half of the OFTPs. First OFTP exponential PSA kinetic was associated with a shorter time to CRPC and worse CSS. Prostate 76:13–21, 2016 . © 2015 Wiley Periodicals, Inc.